IJCM_361A: Mindful Memories: Breaking the Silence on Alzheimer's: Awareness on Alzheimer's disease among health care workers in Shimla City - Kaushal Anuj; Sachdeva Amit; Kaushal Anuj (Wolters Kluwer Medknow Publications, 2024)
Background: Alzheimer's disease is the most common type of dementia which is a progressive disease beginning with mild memory loss and possibly leading to loss of the ability to carry on a conversation and respond to the environment. Currently more than 55 million people have dementia worldwide, over 60% of whom live in low-and middle-income countries. Objectives: This study aims to assess the level of knowledge regarding Alzheimer's Disease among healthcare workers in Shimla District. Methodology: It was a cross-sectional study conducted from September to October 2023 in Shimla region. The participants were invited openly through social media platform (e.g. WhatsApp, Facebook, Instagram) by sending Google form links, we obtained total of 400 responses. Responses were then recorded in a Google Excel spreadsheet, the information from which was used to generate graphical display. Statistical analysis was done by using Epi Info 7. Results: Around 52% of healthcare workers had good knowledge regarding the disease and around 25% had very good knowledge regarding the same. Most of the participants belonged to the age group of 18-30 years and results were found to be statistically significant in this case. Education played an important role and was found to be statistically significant. Conclusion: Awareness among healthcare workers is important as they can screen the patients early, educate them, and refer them when needed. Medical management can improve the quality of life for individuals and for their caregivers.